GAMBARAN PENGGUNAAN OBAT TRADISIONAL UNTUK PENYAKIT HIPERTENSI PADA MASYARAKAT KELURAHAN BUDAYA PAMPANG KECAMATAN SAMARINDA UTARA - Septiana Dewi; Dwi Elfira Kurniati; Lizma Febrina (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2024)
The Budaya Pampang community still adheres to the tradition of using traditional medicine. This is interesting to study, especially in hypertension which has a high prevalence. This study aims to determine the characteristics of the Budaya Pampang Village community who use traditional medicine for hypertension and the pattern of using traditional medicine for hypertension in the community. This research is a descriptive study with total sampling technique. Data collection was carried out using a questionnaire given to 48 respondents. Data were analyzed by descriptive statistics using SPSS. The results showed that the characteristics of the most respondents were male (54.2%), aged >45 years (81.2%), elementary school education (41.7%), housewife occupation (39.6%), duration of hypertension >1 year (77.1%), and duration of taking traditional medicine >1 year (64.6%). The most widely used plant type was bay leaf (16.7%), the most common dosage form was fresh preparation (91.7%), the most common processing method was boiling (68.7%), the frequency of use was 2x a day (43.8%). The reason for using traditional medicine is because it is cheaper (89.6%), easy to obtain or grow yourself (81.3%), and easy to prepare or mix (79.2%). Based on the results of the study, there are 16 species of medicinal plants with antihypertensive properties that can be the basis for drug development in the future.